A new species of Bomarea (Alstroemeriaceae) from the northwestern slopes of the Ecuadorian Andes - Fierro-Minda, Alisson; Tobar, Francisco; Cevallos, Daniela; Burgess, Kevin S.; Pérez, Álvaro J. (Phytotaxa, 2024)
Bomarea quitensis, a new endemic species from Pichincha Province, is described. Due to its long pedicels (11.0–12.5 cm), this new species belongs to B. subgenus Bomarea. Bomarea quitensis is related to B. longipes and B. crinita but differs from these species in leaf shape and size, number of flowers and colour of the sepals. Photos of all its structures and a distribution map are presented; additionally, the conservation status of B. quitensis is assessed.